DISTINGUISHING LEGAL POLICIES ON HADHANAH DETERMINATION IN INDONESIA - Ari Hidayat, Muhammad Yayad; Fadhli, Muhammad; Aribbilah, Ilhamuddin; Susandi, Ari; Saiin, Asrizal (Borneo Law Review, 2024)
Childcare, or hadhanah, is an important aspect of the family system that plays a crucial role in the development and well-being of children. In Indonesia, a country with a rich diversity of cultures, religions and customs, hadhanah practices can vary significantly across regions. This variation is due to differences in social norms, cultural values, as well as interpretations of religious law, particularly Islamic law. Hadhanah in Islamic law regulates the rights and responsibilities of parents or other parties in caring for children after divorce or the death of one of the parents. Although the basic principle is the best interest of the child, its implementation is often influenced by the local context. For example, in Muslim-majority areas, hadhanah practices are heavily guided by sharia provisions, while in other areas, local customs and traditions also play an important role. This study aims to uncover the differences in the implementation of hadhanah in different regions, as well as identify the challenges faced by families in parenting children in different contexts. The method used in this research is library research. The results show that the issue of childcare (hadhanah) has differences in each region, this is a factor of the diversity of culture, religion and customs in each region. Keywords: childcare, hadhanah